Mawlawi’s Book of Poems: Horami spoken variety or Gorani literary variety? - Mirani), Jabar Khidr Muhammad (Jabar (Sulaimani Journal for Humanities, 2025)
Horami spoken variety (HSV) and Gorani literary variety (GLV) are subsumed under the more comprehensive dialect of Gorani-Zaza of Kurdish language. Some mistakenly consider these two as the same and they treat the Book of Poems of poets like Mawlawi as HSV; howevere, this article aims to prove that Mawlawi’s Book of Poems (MBP) differs from HSV in terms of some distinctive linguistic features of phonetics and phonology, syllable design, morphology, lexicon, syntax and semantics. HSV has two more phonemes, i.e. two consonants (ɹY) and (N), non-existent in GLV. HSV has three initial and final consonant clusters absent in GLV. Morphologically, word formation mechanisms for making gerund, plural, … are somehow different in these two varieties. Furthermore, the objective, accusative, possessive (izafe), and locative case-markers have overt realizations in HSV while they are not realized in MBP. Moreover, comparing their lexicon based on 100 Swadesh’s word list shows the existence of about 50 common and similar, and nearly 50 different words in these two varieties. Syntactically, they represent somehow various formal features of person, number and gender agreement in both accusative-nominative and absolutive-ergative case-marking patterns. Morover, the signs of female gender and direct object and obliques are only perceived in HSV. As the result, this study highlights more structural differences between HSV and GLV of Mawlawi and it provides more support for this view that the variety present in MBP is GLV and not HSV.
Keywords: Horami spoken variety; Gorani literary variety; GoranZaza dialect; distinctive linguistic features